Current status and future prospects of membrane separation processes for value recovery from wastewater. (March 2022) - Kavitha, E.; Poonguzhali, E.; Nanditha, D.; Kapoor, Ashish; Arthanareeswaran, G.; Prabhakar, S.
Abstract: Resource constraints and deteriorating environment have made it necessary to look for intensification of the industrial processes, to recover value from spent streams for reuse. The development of reverse osmosis has already established that water can be recovered from aqueous streams in a cost-effective and beneficial manner to the industries. With the development of several membrane processes and membrane materials, the possibility of recovering value from the effluents looks like a workable proposition. In this context, the potentialities of the different membrane processes in value recovery are presented. Among the pressure-driven processes, reverse osmosis can be used for the recovery of water as value. Nanofiltration has been used for the recovery of several dyes including crystal violet, congo red, methyl blue, etc., while ultrafiltration has been used in the fractionation of different solute species using membranes of different pore-size characteristics. Diffusion dialysis is found useful in the separation of acids from its salt solutions. Bipolar membrane electrodialysis has the potential to regenerate acid and base from salt solutions. Thermally driven membrane distillation can provide desalinated water, besides reducing the temperature of hot discharge streams. Passive membrane processes such as supported liquid membranes and membrane-assisted solvent extraction have been found useful in separating minor components from the wastewater streams. The details are discussed to drive home that membrane processes can be useful to achieve the objectives of value recovery, in a cost-effective manner through process intensification, as they are more compact and individual streams can be treated and value used seamlessly. Graphical abstract: Image 1 Highlights: Isolation of wastewater stream at source for easy recovery of value. Trace metal recovery through size enhanced ultrafiltration. Removal and recovery of organic species through membrane solvent extraction. Process intensification through membrane processes.